2011
DOI: 10.1563/aaid-joi-d-09-00114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bisphosphonates on Alveolar Bone Loss Around Osseointegrated Implants

Abstract: The relationship between bisphosphonates (BP) and dental implant failure has not been fully elucidated. The purpose of this retrospective radiographic study was to examine whether patients who take BP are at greater risk of implant failure than patients not using those agents. Treatment records of 362 consecutively treated patients receiving endosseous dental implants were reviewed. The patient population consisted of 227 women and 135 men with a mean age of 56 years (range: 17-87 years), treated in the Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 72 publications
0
52
1
4
Order By: Relevance
“…BP effect to the implantation success did not show any statistically significant differences in various studies [21,24,25,30,31]. However, Zahid et al [25] showed high correlation between the BP usage and implant thread exposure (P = 0.001) among the 51 implants.…”
Section: Resultsmentioning
confidence: 92%
“…BP effect to the implantation success did not show any statistically significant differences in various studies [21,24,25,30,31]. However, Zahid et al [25] showed high correlation between the BP usage and implant thread exposure (P = 0.001) among the 51 implants.…”
Section: Resultsmentioning
confidence: 92%
“…The evaluation of dentures vs. implants. It is suggested to not place immediate implants in patients with antiresorptive therapy, atraumatic surgery with perioperative antibiotics, the necessity of a recall and the avoidance of bone augmentations Grötz 2010 [54]ReviewThe authors provide an algorithm how to proceed with patients receiving BP seeking implant therapy.The authors state the necessity for an individual risk assessment and avoidance of bone augmentations Krimmel 2014 [55]RS50 patients with BP-ONJDMFT of all patients 20.5 ± 4.2disease free interval for patients with DMFT < 20: 39.7 ± 1.1 monthsdisease free interval for patients with DMFT > 20: 14.4 ± 2.8 monthsThe DMFT had no influence on the overall healing rate of BP-ONJ Tsao 2013 [56]CCS63 patients22 BP-ONJ patients41 matched controlsCaries similar between groupsPeriodontal disease associated with BP-ONJ (pocket depth, IgG serum titer against Porphyromonas gingivalis, IL 1ß level in gingival cervical fluid) Thumbigere-Math 2013 [57]CCS73 patients25 BP-ONJ patients 48 matched controlsBP infusions BP-ONJ 38.4 and control 18.8BP-ONJ vs control:missing teeth: 7.8 vs 3.1clinical attachment level: 2.18 vs 1.56radiogic bone loss at teeth > 50%: 20% vs. 6% Martin 2010 [58]CSS8,752 patients with oral BP returned dental survey (62% response rate)589 patients with dental implants16 patients with 26 implant failures8 patients with failure of 12 implants in the maxilla9 had failure with 14 implants in the mandible Shabestari 2009 [59]RS21 female osteoporotic women with oral BP and 46 implantsNo BP-ONJ, no signs of peri-implantitis Zahid 2011 [60]RS362 patients with implants26 BP patients with 51 implants3 implants failedPatients with BP had more thread exposure Memon 2012 [61]RS200 patientsBP: 100 women with 153 implantscontrol: 100 women with 132 implantsSuccess equal for both groups 93.5 (BP) vs. 95.5 (control)crestal bone change from implant insertion to stage two surgery: no difference between the groups Yip 2012 [62]CCS337 patients 114 patients with implant failure223 patients without implant failure% of patients using BPImplant failure group: 9.65%no implant failure: 4.04 Walter 2014 [3]RS504 patients with osteonecrosis227 with BP-ONJ7 out of 227 patients with BP-ONJ implant as trigger factor…”
Section: Resultsmentioning
confidence: 99%
“…Other cohort studies showed minor risks of osteopathology development in patients receiving oral BP therapy and dental implant insertion. On the other hand, the local and short-term use of BP has been shown to have a positive influence on osseointegration of all implants, dental or otherwise [12,13].…”
Section: Introductionmentioning
confidence: 99%